The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.celrep.2017.01.078
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 Controls Timely MyoD Expression via MyoD Core Enhancer Transcription

Abstract: MyoD is a master regulator of myogenesis. Chromatin modifications required to trigger MyoD expression are still poorly described. Here, we demonstrate that the histone demethylase LSD1/KDM1a is recruited on the MyoD core enhancer upon muscle differentiation. Depletion of Lsd1 in myoblasts precludes the removal of H3K9 methylation and the recruitment of RNA polymerase II on the core enhancer, thereby preventing transcription of the non-coding enhancer RNA required for MyoD expression (CEeRNA). Consistently, Lsd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 48 publications
8
66
0
2
Order By: Relevance
“…In injured muscles, increased glycolysis may generate the glycolytic intermediates necessary for the production of new biomass and metabolites utilized by histone-and DNA-modifying enzymes whereas oxidative phosphorylation would generate the ATP required for MuSC proliferation (Ryall et al, 2015a;Pala et al, 2018). Indeed, metabolites generated by different metabolic pathways regulate the activity of chromatin-modifying enzymes known to control different aspects of MuSC biology (McKinnell et al, 2008;Juan et al, 2011;Kawabe et al, 2012;Liu et al, 2013;Ryall et al, 2015b;Boonsanay et al, 2016;Faralli et al, 2016;Scionti et al, 2017;Das et al, 2017;Tosic et al, 2018;Puri and Mercola, 2012). For instance, the oscillation of intermediary metabolites of the NAD biosynthetic pathways may be relevant for circadian gene expression in MuSCs and skeletal muscle (Nakahata et al, 2009;Ryall et al, 2015b;Solanas et al, 2017;Andrews et al, 2010;Lowe et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In injured muscles, increased glycolysis may generate the glycolytic intermediates necessary for the production of new biomass and metabolites utilized by histone-and DNA-modifying enzymes whereas oxidative phosphorylation would generate the ATP required for MuSC proliferation (Ryall et al, 2015a;Pala et al, 2018). Indeed, metabolites generated by different metabolic pathways regulate the activity of chromatin-modifying enzymes known to control different aspects of MuSC biology (McKinnell et al, 2008;Juan et al, 2011;Kawabe et al, 2012;Liu et al, 2013;Ryall et al, 2015b;Boonsanay et al, 2016;Faralli et al, 2016;Scionti et al, 2017;Das et al, 2017;Tosic et al, 2018;Puri and Mercola, 2012). For instance, the oscillation of intermediary metabolites of the NAD biosynthetic pathways may be relevant for circadian gene expression in MuSCs and skeletal muscle (Nakahata et al, 2009;Ryall et al, 2015b;Solanas et al, 2017;Andrews et al, 2010;Lowe et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In brief, LSD1 was implicated in spermatogenesis [62,63] and adipogenesis [64,65], while its loss promoted differentiation of mesenchymal stem cells towards bone or liver [66][67][68][69][70][71]. In a different context, LSD1 was required by the satellite cells (stem cells of muscle) for myogenic regeneration after injury [72] or for proper myoblast differentiation [73].…”
Section: Lsd1 In Other Normal Stem Cell Typesmentioning
confidence: 99%
“…In other cases, however it has been shown that Lsd1 is involved in demethylation of H3K9 or H4K20 and can act as a transcriptional co-activator (15)(16)(17)(18). Loss of Lsd1 in all cells leads to early lethality in mice (15), whereas tissue specific manipulations of Lsd1 function revealed roles in the development and homeostasis of several organs and cell types (15,(19)(20)(21)(22)(23)(24)(25)(26)(27). Lsd1 has been shown to be particularly important in the nervous system where it regulates neurogenesis at several levels.…”
Section: Introductionmentioning
confidence: 99%